Social exclusion and collaborative governance networks: The Muslim minority dilemma between participation and coercion - Χωριανόπουλος, Ιωάννης (The Greek Review of Social Research, 2013)
This article explores the EU approach to social exclusion in urban areas. It looks at Komotini, focusing on the city’s Muslim minority, and at local efforts to tackle social exclusion through enhanced participatory governance. The notion of «citizenship rights» guided intervention, bringing forward the distinction between the de jure and the de facto rights enjoyed by the local minority. Notwithstanding, power asymmetries between partners question the «empowering» potential that polycentric governance holds for the minority community. Drawing from the relevant debate, the article discusses the minority options of governance participation and all-out opposition of such schemes.